Strategi Gastrodiplomasi Indonesia Melalui Kopi - Iqbal, Muhammad; Darman Moenir, Haiyyu; Elian Nasir, Putiviola (Hubungan Internasional Universitas Andalas, 2024)
Indonesia has long been engaged in coffee gastrodiplomacy, but its efforts have yet to reach their full potential. In 2018, during the administration of President Joko Widodo, Indonesia renewed its focus on coffee gastrodiplomacy. This research aims to illustrate various initiatives in coffee gastrodiplomacy undertaken by Indonesia from 2012 to the present. Indonesia has revitalized its coffee gastrodiplomacy due to the global trend of coffee consumption and the popularity of Indonesian coffee commodities in the international market, characterized by their unique and distinctive flavors. This study utilizes the concept of gastrodiplomacy strategy proposed by Juyan Zhang to analyze Indonesia's efforts in coffee gastrodiplomacy. The methods employed include descriptive analysis and the application of Juyan Zhang's gastrodiplomacy strategies, namely Product Marketing Strategy, Food Event Strategy, The Coalition-Building Strategy, The Use of Opinion Leaders Strategy, The Media Relations Strategy, and The Education Strategy. The results of this research delineate various diplomatic efforts through coffee undertaken by Indonesia. It is evident that Indonesia's coffee gastrodiplomacy efforts are predominantly characterized by the Food Event Strategy. In terms of The Use of Opinion Leaders Strategy and The Media Relations Strategy, there is still room for improvement. However, Indonesia has performed reasonably well in other strategies. Indonesia's coffee gastrodiplomacy has a direct impact on the value and volume of Indonesian coffee exports. Before 2018, there were fluctuations in the value and volume of coffee exports. However, post-2018, there has been a gradual increase in both the value and volume of coffee exports, in line with the growing variety and intensity of Indonesia's coffee gastrodiplomacy efforts.